Synthesis of NiFe2O4 using degreasing cotton as template and its adsorption capacity for Congo Red. Issue 24 (20th May 2016) - Kong, Chao; Li, Jia; Liu, Futian; Song, Yi; Song, Peng
Abstract: In this contribution, the biomorphic NiFe2 O4 was synthesized by using degreasing cotton as template via a simple one-step process involving impregnation and calcination. The obtained samples were characterized by X-ray diffraction patterns (XRD), scanning electron microscope (SEM), alternating gradient magnetometer and nitrogen adsorption–desorption isotherms. It was found that the as-prepared samples retained the characteristic hollow fiber morphology of the degreasing cotton template, and were composed of NiFe2 O4 nanoparticles with the grain size ranging from 5 to 20 nm. The Brunauer Emmett Teller (BET) specific surface area and pore volume of the obtained sample were 118.620 m 2 g −1 and 0.303 cm 3 g −1, respectively. In addition, the Congo red (CR) adsorption performances of the obtained samples were also evaluated. The effects of calcination temperature and pH on CR adsorption were discussed. The results showed that the best adsorption performance (89.45 mg g −1 ) was obtained when the calcination temperature was 600°C. The process of CR adsorption was spontaneous, exothermic and favorable, and was well described by both the Langmuir isotherm model and the pseudo-second-order kinetics model. The obtained sample was effective in adsorbing CR in the neutral and acidic conditions. Electrostatic attraction between samples and CR molecules was the main reason of the high adsorption.